A clinical study comparing self ligating brackets (Damon system) with conventional brackets on accelerating alignment and leveling in a sample of adult patients - حسن, حازم; خليل, فادي; رقيه, علي (Latakia University Journal -Medical Sciences Series, 2021)
Professor - Department of Operative Dentistry - Faculty of Dentistry